Protein level affects the relative lysine requirement of growing rainbow trout (Oncorhynchus mykiss) fry - Bodin, Noelie; Govaerts, Bernadette; Abboudi, Tarik; Detavernier, Christel; De Saeger, Sarah; Larondelle, Yvan; Rollin, Xavier (British Journal of Nutrition, 2009)
The effect of two digestible protein levels (310 and 469g/kg DM) on the relative lysine (Lys; g Lys/kg DM or g Lys/100g protein) and the absolute Lys (g Lys intake/kg(0.75) per d) requirements was studied in rainbow trout fry using a dose-response trial. At each protein level, sixteen isoenergetic (22-23 MJ digestible energy/kg DM) diets were tested, involving a full range (2-70 g/kg DM) of sixteen Lys levels. Each diet was given to one group of sixty rainbow trout fry (mean initial body weight 0.78g) reared at 15 degrees C for 31 feeding d. The Lys requirements were estimated based on the relationships between weight, protein, and Lys gains (g/kg(0.75) per d) and Lys concentration (g/kg DM or g/100 g protein) or Lys intake (g/kg(0.75) per d), using the broken-line model (BLM) and the non-linear four-parameter saturation kinetics model (SKM-4). Both the model and the response criterion chosen markedly impacted the relative Lys requirement. The relative Lys requirement for Lys gain of rainbow trout estimated with the BLM (and SKM-4 at 90% of the maximum response) increased from 16.8 (19.6) g/kg DM at a low protein level to 23.4 (24.5) g/kg DM at a high protein level. However, the dietary protein content affected neither the absolute Lys requirement nor the relative Lys requirement expressed as g Lys/100g protein nor the Lys requirement for maintenance (21 mg Lys/kg(0.75) per d).